2003
DOI: 10.1046/j.1365-2699.2003.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Rain forest expansion mediated by successional processes in vegetation thickets in the Western Ghats of India

Abstract: Aim The objective of this study was to document succession from grassland thickets to rain forest, and to provide evidence for their potential as restoration tools.Location The Linganamakki region (State of Karnataka) of the Central Western Ghats of India.Method We selected thirty vegetation thickets ranging from 4 to 439 m 2 in area in the vicinity of rain forest. The area of each small thicket was estimated as an oval using its maximum length and its maximum width. When the shape was irregular (mostly in lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 28 publications
2
41
0
3
Order By: Relevance
“…Yarranton and Morrison (1974) referred to the initial colonists as ''nuclei'', and the process of cluster development and expansion as ''nucleation'', analogous to the use of the terms in the physical sciences. Once a persistent colonist establishes, further colonization within a nucleus can be facilitated via capture of wind-blown seeds (Yarranton and Morrison, 1974;Del Moral and Bliss, 1993;Franks, 2003) or attraction of birds or other animals that may disperse seeds (Cabral et al, 2003;Carriè-re et al, 2002b;Fuentes et al, 1986;Guevara et al, 1986;McDonnell and Stiles, 1983;Puyravaud et al, 2003;Slocum, 2001).…”
Section: Nucleation As a Natural Processmentioning
confidence: 99%
“…Yarranton and Morrison (1974) referred to the initial colonists as ''nuclei'', and the process of cluster development and expansion as ''nucleation'', analogous to the use of the terms in the physical sciences. Once a persistent colonist establishes, further colonization within a nucleus can be facilitated via capture of wind-blown seeds (Yarranton and Morrison, 1974;Del Moral and Bliss, 1993;Franks, 2003) or attraction of birds or other animals that may disperse seeds (Cabral et al, 2003;Carriè-re et al, 2002b;Fuentes et al, 1986;Guevara et al, 1986;McDonnell and Stiles, 1983;Puyravaud et al, 2003;Slocum, 2001).…”
Section: Nucleation As a Natural Processmentioning
confidence: 99%
“…Especially due to the heavy rainfall, western facing portions of the mountains would have been covered with tropical evergreen forests, laced with water courses and swamps [24,27]. Earlier studies in the Western Ghats also showed that remnants foster successional processes in natural restoration of rainforests [32]. Shifting cultivation was a major activity of forest dwelling tribals, throughout the Western Ghats, sparing only the higher altitudes.…”
Section: The Value Of Forest Patchesmentioning
confidence: 99%
“…There are fewer studies finding such an increase in tropical savannas, but some do exist: for example in northern Australia (Hopkins et al 1996;Bowman et al 2001;Russell-Smith et al 2004;Brook and Bowman 2006), the Western Ghats of India (Puyravaud et al 2003), and South America Durigan and Ratter 2006;Marimon et al 2006;Roitman et al 2008). In Africa just four studies showing increasing tree cover in tropical rain forestsavanna boundary regions have been reported.…”
Section: Introductionmentioning
confidence: 99%